Pelaksanaan Program Nasional Pembuatan Sertifikat Tanah Bagi Masyarakat Miskin di Desa Talumae Kecamatan Watang Sidenreng Kabupaten Sidenreng Rappang - Hasim Hasim (PRAJA: Jurnal Ilmiah Pemerintahan, 2028)
Abstract This research was conducted at TalumaE Village of Watang Sidenreng District in Sidenreng Rappang Regency, from the beginning of national program provided freely by the government for the poor but was falsely utilized by some parties to collect funds from the public. And so the poor didn’t acknowledge the procedures required, this program was utilized by others who did. The research was a type of descriptive-qualitative study, population took as many as 315 people, fifteen percent (15%) or 32 people of them were taken into samples. Data collection methods used were interviews, observation, literature study and analyzed using descriptive data analysis. The results for the Implementation of the National Program for Soil Preparation Certificate for the Poor at TalumaE Village of Watang Sidenreng District in Sidenreng Rappang Regency was rated 41,28%. While the affecting factors were rated 45,63%.